Efektivitas Lembar Kerja Berbasis PBL terhadap Hasil Belajar Siswa pada Materi Ekosistem - Fadhilah, Sairotul; Nur Aeni, Eka; Nurahmawati, Isma (Jurnal Pendidikan dan Ilmu Fisika, 2025)
This study investigates the effectiveness of Student Worksheets based PBL (Problem-Based Learning) in improving the science learning outcomes of third-grade elementary school students, specifically on the topic of ecosystems. A quasi-experimental design with a pretest-posttest control group was employed, involving two purposively selected classes: the experimental group used Student Worksheets based PBL, while the control group utilized conventional LKPD with traditional teaching methods that did not integrate problem-solving activities. The learning outcomes were assessed through written tests and analyzed using independent t-tests to determine significant differences between the groups. The results revealed that students who used Student Worksheets based PBL demonstrated significantly better science learning outcomes compared to those who used conventional LKPD. This finding highlights that Student Worksheets based PBL is effective in enhancing students' conceptual understanding and problem-solving abilities, especially in ecosystem topics. The study's limitations include a small sample size and a brief intervention period. In practical terms, the findings suggest that Student Worksheets based PBL can be a valuable and engaging alternative learning tool, while socially, it promotes the development of active and creative learning environments in elementary education.